The Genealogy of Prophets from a Gender Perspective - Muh. Yunan Putra; Nurdiniawati Nurdiniawati; Ainun Rahma Daniah; Muh. Zulkarnain (STIT Sunan Giri Bima, 2025)
This study aims to map the prophetic genealogical values manifested in the Rimpu tradition, starting from the role of teachers and traditional leaders in producing the meaning of rimpu, and the implications of the rimpu tradition for strengthening women's agency in Bima. This study uses ethnographic methods through participatory observation, in-depth interviews with women practitioners of Rimpu, tuan guru, and cultural experts, as well as visual documentation. Data sources were determined using purposive sampling techniques and analyzed using the interactive analysis model steps from Miles, Huberman & Saldana, including data collection, data condensation, data presentation, and conclusion drawing. The research data was analyzed using Nvivo 12 software. The results of the research and findings of the analysis revealed several key points, including: (1) The tradition of rimpu for women in Bima, genealogically reflects prophetic values such as religious values, values of modesty, moral values, values of obedience, and cultural values; (2) Teachers and cultural figures play a role in stimulating the existence of the rimpu tradition for women in Bima through various activities, ranging from religious lectures, rimpu education, cultural festivals, seminars, and cultural dialogues; (3) The rimpu tradition has positive implications for women's gender attitudes, such as being respected, protecting themselves, maintaining modesty, and educating women's character in Bima society